Evaluation of two methods for mixed dentition analysis using the method error - Bruna Santos da Cruz; Eduardo Kant Colunga Rothier; Beatriz de Souza Vilella; Oswaldo de Vasconcellos Vilella; Rizomar Ramos do Nascimento (Universidade Estadual de Campinas, 2015)
The most commonly used tests to assess the mesiodistal width of the unerupted permanent canines and premolars are divided in two groups: those performed directly on plaster models, using mathematical equations that can generate tables, and those using radiographs. Aim: In order to determine the reliability between two of these methodologically different method, this study evaluated the systematic and random errors of the method proposed by Tanaka and Johnston, which is based on the sum of mandibular permanent incisors, and the Huckaba method, which uses radiographs. Methods: In a random sample of 28 plaster models of mandibular dental arches belonging to individuals of both genders, aged six to eleven years old, a single investigator performed the measurement of required space, according to the two methods evaluated. After 15 days, the measurements were repeated, and each of them was performed twice in sequence to calculate the repeatability and reproducibility conditions, and the systematic and random errors for each method. Results: The random error of the method proposed by Huckaba was larger in terms of reproducibility (1.53 mm) and repeatability (0.57 mm) compared with the analysis proposed by Tanaka and Johnston (0.20 mm and 0.12 mm, respectively). Conclusions: The method proposed by Huckaba was proved to be inadequate in relation to reproducibility, with respect to the random error, and should be used with caution to measure the required space in the mandibular arch.